Influence of Nitridation on Structural and Photoluminescence Behaviour of CaZrO3:Eu3+ Nanophosphors - Kumar, S.G. Prasanna; Kottam, Nagaraju; Krishna, R. Hari; Prabha, M.N. Chandra; Preetham, R.; Behara, Santosh; Thomas, Tiju (Asian Journal of Chemistry, 2020)
Ca1-xZrO3:xEu3+ (x = 0.05) phosphors have been prepared by using the low temperature solution combustion synthesis. The prepared nano phospors are well characterized by powder X-ray diffraction, scanning electron microscopy, Fourier infrared spectroscopy and transmission electron spectroscopy. PXRD results showed orthorhombic phase and SEM images showed porous agglomerated morphology. Influence of nitridation on structural and photoluminescence properties of the phosphor were investigated for wide range of nitridation time. The photoluminescence (PL) intensity was found to vary with nitridation with small shift in the photoluminescence emission peaks. The probable reasons for the variation of photoluminescence with nitridation are discussed.